Long-term debt sustainability in emerging market economies: A counterfactual analysis - Ugo Panizza (Graduate Institute of International and Development Studies, 2022)
The 2015 Addis Ababa Action Agenda recognized the need for policies aimed at maintaining longterm debt sustainability. This paper describes a set of commonly used definitions of debt sustainability and shows that none of them focuses on long-term debt sustainability. It then discusses concept and several practical and conceptual difficulties linked to assessing solvency in developing and emerging countries. Next, the paper asks whether countries default because they borrow too much, or because investors think that they will default and this expectation becomes self-fulfilling. To answer this question, the paper uses a sample of 17 emerging market countries over 1970-2020 to build counterfactual debt levels under the assumption that these countries had continuous access to the international capital market without paying any premium over US Treasuries. The exercise shows that most debt crises are not driven by solvency issues.
Keywords: F34; F32; H63; 330; Public debt; Default; Liquidity crises